Ethio-Telecom Reform: An Assessment from the Perspective of Homegrown Economic Reform and the Imperatives of Economic Globalization - Tulu, Diriba Adugna (Hasanuddin Journal of International Affairs, 2024)
This article explores the Ethio-Telecom reform within the context of the Homegrown Economic Reform (HGER) initiated by the Ethiopian government and the imperatives of economic globalization. Its main objective is to analyze the extent to which the Ethio-Telecom reform within the HGER agenda is genuinely homegrown and new by considering internal dynamics and external influences. In order to achieve the intended aims, the article employed a qualitative approach, which includes the analysis of existing work surveys and document examination. To this end, the work has relied primarily on secondary data sources. The article argues that the Ethiopian HGER, with a specific focus on the Ethio-Telecom sector reform, reflects a mix of endogenous factors and external influences, with ongoing debates regarding its authenticity and alignment with domestic priorities. Moving forward, it should balance external support with local perspectives to avoid being perceived as a replication of external models.